Defining the patterns of a jet takeoff system operation in an aerial vehicle with nozzles of a special shape, powered by a gas-hydraulic accumulator - Strutinskiy, Serhii; Kostiuk, Dmytro; Gryshko, Igor; Zilinskyi, Andrii (Eastern-European Journal of Enterprise Technologies, 2026)
This paper investigates working processes in a liquid nozzle system powered by a gas-hydraulic accumulator used for aircraft takeoff. The study is aimed at finding regularities in the operation of a hydraulic system, which includes a gas-hydraulic accumulator and nozzles with a variable cross-sectional shape that operate at variable pressure. These regularities determine the kinematic parameters of an aircraft that is propelled by a liquid nozzle system. Numerical modeling of the working processes in nozzles of a special shape showed an increase in vortex formation and a more dramatic increase in the velocity in the flow core at the end section of the nozzle. It was established that energy losses for nozzles with a variable cross-sectional shape are 4% greater than for conical nozzles. The established patterns of the gas-hydraulic accumulator charging and discharging processes have made it possible to determine the optimal ratio between the mass of the liquid and the filled accumulator, equal to 0.23. It is shown that the maximum amount of energy and liquid is obtained when the nozzles operate at a variable pressure that falls below the initial charging pressure. Based on the nozzle thrust, dependences of the takeoff height, speed, and acceleration of the aircraft on its mass were determined. It was found that at a ratio of aircraft mass to the mass of the gas-hydraulic accumulator of 2.0, the nozzle system provides only horizontal acceleration to the breakaway speed, and when the ratio is less than 0.2, vertical lift and horizontal acceleration to the breakaway speed are achieved. The results could be used to assess the maximum capabilities of a takeoff system when applying water as the working fluid.